Surge Protection for Low Voltage Systems - Rousseau, Alain (Institution of Engineering & Technology, 2021)
Protection of low-voltage electrical and electronic equipment and systems from lightning strikes and other power surges is vital for computing, telecommunications, transportation, power grids, distributed energy and charging installations. This systematic treatise covers surge causes, risk assessment, and protective measures
Keywords: Low voltage systems -- Safety measures.; Transients (Electricity); Electronic apparatus and appliances -- Protection.; elektronické knihy; electronic books